(untitled) (Innovation & Development in Engineering and Applied Science, 2022)
Computer security is a topic that has been gaining strength in the last decade, this because it is worrying the possibility that the government or companies outside the law to monitor citizens. Spyware, a software that does nothing more than violate the privacy of people who unfortunately are infected with one or more and this is done in a hidden and quite silent way. So it is of utmost importance to know, recognize and even determine how to fight against these tiny cyber threats. This small software leaks, searches and steals information abruptly, which could cause financial catastrophes in a family, or in a company, selling information or taking advantage of all the stolen content to wreak havoc. Although some Spyware developers sell their product as a way to control employees, it does not detract from the fact that their program handles the same operation as if to do evil.